Effect of Mesenchimal Stem Cells on Apoptosis Indices in Renal Parenchyma during Experimental Stress - Elena V. Demianenko; Aleksandr I. Glukhov; Galina K. Gryzunova (Acta Biomedica Scientifica, 2019)
Background. Kidneys are extremely sensitive to various environmental factors. Stress disturbs prooxidant-antioxidant balance, causes hyperproduction of reactive oxygen species, changes activity of the nitroxidergic system components, regulating apoptosis. The use of mesenchymal stem cells can normalize functioning of damaged organs in the pathological process.Aim: to assess the effectiveness of mesenchymal stem cells in a single 24-hour immobilization according to the dynamics of apoptosis indices in renal tissue – nitric oxide (NO) and fragmented DNA.Materials and methods. The study included male nonlinear white rats aged 3 to 4 months and weighing 225 ± 25 grams. Experimental stress was modeled by the immobilization of animals in the fixation chambers within 24 hours. The efficacy of cell therapy was determined by the change in the concentration of the tested substances at 1, 3, 7, 14, 21 and 30 days of the experiment.Results. There was a sharp increase in the total amount of nitrates / nitrites and the level of DNA fragmentation in the homogenates of the renal parenchyma after the action of an acute stressor, which may indicate the induction of apoptosis. It was proved that in animals, receiving mesenchymal stem cells as a treatment, the restoration of the studied parameters in the kidney tissue was significantly accelerated in comparison with the controls values.Conclusion. Mesenchymal stem cells protect cells from self-destruction and activate reparation, which makes them promising for further study.